(3HjGf LgO Gdebds - (3GdeQYTj, SGLbdj RGOg, eMeO Hf CHi HcQ, J(B1145(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj Yde GdbQBf hNdbfG hYdefG GdHjGf hHYO ajbhd GdHGFS GdabjQ eMeO GdeQYTj GdedbH HSGLbdj RGOg deG NJeJ QSGdJj GdeSeGI HLgO Gdebd TQMJgG s
(3BNQgG (B:s
(3hGdCeQ djS cPdc dCf jGA jgeG ef faS GdcdeI dG jGA EVGaI , bhdg GdHWGdI HaJM GdHGA HeYfi GdJYWd hGdeQGO eMHI GdJYWd hGdGSJKbGd (B( (3cPG (B) (3GdGTJZd HGdYde , bhdg (B: (3Ydi GdJVLQ hgh JVjjb GdbdH hGVWQGHg HSHH GdZe , bhdg JJe GdUGdMGJ Cj GdCYeGd GdUGdMIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3 / 711s
(3EjVGM Gdecfhf (B1 / 387s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs